Psychological ownership and affective reaction: Emotional attachment process variables and the endowment effect - Shu, Suzanne B.; Peck, Joann (Journal of Consumer Psychology, 2011)
AbstractThis research proposes that the concept of emotional attachment, and specifically the independent constructs of psychological ownership and affective reaction, can help explain many of the endowment effect findings documented in the literature. We define these constructs and then test them across a set of nine studies in which we both replicate previous and generate new endowment effect findings, and then show that psychological ownership and affective reaction can mediate the effects. In doing so, we offer direct empirical support for the idea of emotional attachment as a driver of loss aversion while also providing practitioners and future endowment effect researchers with new insights about the psychological processes that underlie the endowment effect.